Behavioral Responses to Fossil Fuel Subsidy Reform in Indonesia: A Systematic Review of Economic, Political, and Social Dimensions - Muhamad Iqbal Alferrari Rusmanto (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study presents a systematic literature review on the behavioral changes following fossil fuel subsidy reforms in Indonesia, while also considering the broader economic, political, and social contexts. Using the PRISMA framework, the review analyses 17 selected studies from Scopus-indexed sources with additional reputable reports. The findings reveal significant shifts in household consumption patterns, transportation choices, and energy use, especially among low-income groups. These changes aren’t driven by price signals alone, but also by institutional trust, compensatory mechanisms, and political narratives. The review emphasizes the importance of well-targeted reforms supported by transparent communication and reinvestment strategies to ensure fair and sustainable transitions.